2020
DOI: 10.1038/s41598-020-79799-6
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features of BK-polyomavirus and cytomegalovirus co-infection after kidney transplantation

Abstract: BK polyomavirus (BKPyV) and cytomegalovirus (CMV) are the main viral pathogens affecting the graft and recipient outcome after allogenic kidney transplantation. It has recently been found that infection with both viruses has a greater impact on kidney graft function than a single infection. We retrospectively analyzed a cohort of 723 recipients who received kidney transplantation between 2007 and 2015 after living and postmortal donation for differences in risk and outcome parameters regarding BKPyV (DNAemia) … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 38 publications
1
18
2
Order By: Relevance
“…Cytomegalovirus infection was significantly associated with the development of BKVAN and was also the only risk factor associated with graft dysfunction and graft loss in these patients. Coinfection of BKV and CMV in kidney transplant recipients has been associated with allograft dysfunction in several studies [8,20], comparable to the findings of our study. While there are some data regarding the association of CMV and BKV viremia, data correlating CMV and BKVAN are scarce.…”
Section: Discussionsupporting
confidence: 92%
“…Cytomegalovirus infection was significantly associated with the development of BKVAN and was also the only risk factor associated with graft dysfunction and graft loss in these patients. Coinfection of BKV and CMV in kidney transplant recipients has been associated with allograft dysfunction in several studies [8,20], comparable to the findings of our study. While there are some data regarding the association of CMV and BKV viremia, data correlating CMV and BKVAN are scarce.…”
Section: Discussionsupporting
confidence: 92%
“…The current study showed that more than 40% of viruria co-infection episodes were related to CMV and BK, which contrasted with Jehn et al, who showed that although CMV and BK accounted for most RTx patients, the CMV and BK co-infection were rare [ 10 ]. Our study illustrated that in RTx patients who were routinely screened for viruria, those with late detection had lower risk of repeated BKV, JCV, and CMV viruria infection than those with early detection.…”
Section: Discussioncontrasting
confidence: 78%
“…The current evidence identified risk factors for each single viruria or co-infection. Potential risk factors of viral infection included the age of recipients at renal transplantation time, sex, renal function, donor age, deceased donor, immunosuppressive therapy, and co-morbidities [ 10 , 14 – 16 , 19 ]. Our study showed a negative association between age and risk of viruria infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Risk factors for concurrent viral infections are often related to immunosuppression burden with reported various risk factors of interest outlined in Table 1. CMV donor seropositivity has been strongly identified as a risk factor for coinfection in two large observational studies [odds ratio (OR) 5.35, 95% confidence interval (95% CI) = 2.37–12.0, P < 0.00001; OR 3.97, 95% CI = 1.35–11.6, P = 0.0127] [16 ▪▪ ,17]. Donor/recipient (D/R) CMV serology mismatch was similarly identified as a risk factor (OR 3.648, 95% CI = 1.24–10.7) [17].…”
Section: Renal Transplantmentioning
confidence: 99%